THE EFFECT OF WORKING CAPITAL AND LEVERAGE ON THE VALUE OF FOOD AND BEVERAGES COMPANIES WITH PROFITABILITY AS AN INTERVENING VARIABLE - Kristian Febrianto; Nur Laily (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines and analyzes the effect of working capital and leverage on the firm value of the Food and Beverage companies listed on the Indonesian Stock Exchange (IDX), with profitability as an intervening variable. Furthermore, the working capital was measured by working capital turnover, leverage was measured by Debt to Equity Ratio, profitability was measured by Return On Assets, and firm value was measured by Price to Book Value. The study applies quantitatively, with a causal-comparative approach. Moreover, the data were secondary which in the form of financial statements listed on the IDX. The data collection technique used was purposive sampling with certain criteria and considerations. In line with that, 15 Food and Beverage companies were taken as a sample during 5 years, 2020-2024. In total, there were 75 data samples, which were distributed. Additionally, the data analysis technique used was Structural Equation Modelling (SEM) with Partial Least Squares (PLS) and SmartPLS 4 version. As a result, it shows that working capital has an insignificant effect on profitability. However, leverage has a significantly negative effect on profitability. Also, working capital as well as leverage have an insignificant effect on firm value. In contrast, profitability has a positive and significant effect on firm value. In addition, profitability has an insignificant effect mediates the relationship between working capital on firm value. On the other hand, profitability has a negative and significant effect that mediates fully the relationship between leverage on firm value.